Night-time exploration of a city. Methodological impressions - Darmach, Krystian (A mosaic city: The culture-oriented description, 2023)
In the presented article, I outline the issues related to the night-time aspects of research in a city, and more broadly, the night-time dimensions of anthropological research which, due to its scope and interdisciplinary nature, requires methodological reflection. In an impressionistic form, I outline the problem areas, referring them to both theoretical considerations contained in the literature on the subject and to my own research experience. The text consists of seven fragments, excursions and impressions that are related and correspond to each other on various levels of abstraction.